Morphological characteristics of eyes with neovascular age-related macular degeneration and good long-term visual outcomes after anti-VEGF therapy. Issue 3 (24th September 2021) - Fang, Mengyuan; Chanwimol, Karntida; Maram, Jyotsna; Datoo O'Keefe, Ghazala A; Wykoff, Charles C; Sarraf, David; Brown, A'sha; Lampen, Shaun Ian Retief; Zhou, Brenda; Rusakevich, Alexander M; Sadda, SriniVas
Abstract : Purpose: To analyse the morphological characteristics of eyes with neovascular age-related macular degeneration (AMD) with good long-term visual acuity after anti-VEGF (vascular endothelial growth factor) therapy. Methods: Retrospective, observational study of 175 patients with neovascular AMD with >5 years of follow-up after initiating anti-VEGF therapy. Spectral-domain optical coherence tomography images were assessed for thickness of pigment epithelial detachment (PED), subretinal hyper-reflective material (SHRM), subretinal fluid and subfoveal choroidal, as well as the integrity of the outer retinal bands. Results: The final analysis cohort included 203 eyes (175 patients) followed for a mean of 7.84±1.70 years (range: 5–11). The maximum PED thickness in the foveal central subfield (FCS) was significantly lower (p<0.001) in the poor vision group (13.11 μm) compared with the intermediate (86.25 μm) or good (97.92 μm) vision groups, respectively. In contrast, the maximum thickness of SHRM in the FCS was significantly thicker (p<0.001) in eyes with poor vision (149.46 μm) compared with eyes with intermediate vision (64.37 μm) which in turn were significantly thicker (p<0.001) than eyes with good vision (9.35 μm). The good vision group also had better continuity of all outer retinal bands (external limiting membrane, ellipsoid zone, and retinal pigment epithelium) compared with the other two groups (all p<0.001). Conclusion: A thicker PED and thinner SHRM were correlated with better vision in eyes with neovascular AMD following long-term anti-VEGF therapy. If replicated in future prospective studies, these findings may have implications for design of optimal anatomic endpoints for neovascular AMD treatment.